Poly(acrylonitrile) ultrafiltration membranes. II. membrane morphology and permeation characteristics - Phadke, M. A.; Kulkarni, Sudhir S.; Karode, Sandeep K.; Musale, D. A. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The rheology and phase-boundary characteristics of various solutions comprising three polyacrylonitrile (PAN) grades dissolved in solutions of N,N-dimethylformamide + salt (LiCl, ZnCl2, or AICl(3)) additives were correlated with the resulting membrane morphology as determined by microscopy and permeability measurements. The phase separation characteristics of the dope solution were not markedly affected by the PAN molecular weight (MW); however, they were affected by the salt additive. For higher MW grades, the effect of salt addition can also be masked by the increased self-association tendency of the polymer chains. PAN-B and -C membranes were clearly less asymmetric in structure than the lower MW PAN-Abased membranes. This is attributed to the higher viscosity/lower diffusivity of the PAN-13 and -C solutions, which results in slower solvent-nonsolvent exchange during the phase inversion process. Two factors reduce the incidence of surface defects (increased bubble points): (a) higher solution viscosity dampens surface perturbations during phase inversion, and (b) phase inversion pathways resulting in more homogenous morphology lead to membranes with higher bubble points. (c) 2005 Wiley Periodicals, Inc.
Keywords: bubble point; membranes; Morphology; phase inversion; salts; viscosity